Arthur Miller's "Resurrection Blues": The least Milleresque play? - Ninčetović, Nataša V. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Starting from the observation that Arthur Miller’s “Resurrection Blues” is in many ways unique in comparison to the playwright’s previous oeuvre, we offer evidence that the drama testifies to the evolution of Miller’s style, rather than a change in his focus. The conclusion that Miller’s penultimate play is the least Milleresque is a consequence of its contemporaneity, unusual setting, and adaptation of the topic to contemporary intellectual currents. Although the context of “Resurrection Blues” is undeniably postmodern, the themes that permeate Miller’s entire oeuvre—social criticism, innocence, and guilt—are also crucial to this drama. Тhis paper argues that “Resurrection Blues”, despite being often interpreted as cynical, suggests that the possibility of resistance to the system and redemption exists. However, the play does not imply that a profound change is possible through a political revolution, but only through a change within the individual, i.e. a revolution of consciousness.
Keywords: Arthur Miller; “Resurrection Blues”; social criticism; culpability; innocence